Metody symulacyjne a stochastyczny model polis wieloopcyjnych - Stachura, Michał (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2005)
The paper deals with some possibilities of applications of the Markov chain simulation methods in the live insurance area. Namely as long as Markov processes may be considered as a theoretical model for the multioptional policy notion, one can simulate some sample paths and conclude with the aid of the generated data.The author introduces a very simple Markov chain generation algorithm and uses it in four exemplary policies. It is shown additionally in each case how to built the payment stream of premiums and pays off. Thereby an insurer may use the presented methods as a decisive factor when creating new offer or when selecting new potential clients. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1088, t. 2, s. 254-261